PENGARUH PENGHINDARAN PAJAK TERHADAP BIAYA HUTANG DAN KEPEMILIKAN INSTITUSIONAL SEBAGAI PEMODERASI - FAHREZA UTAMA; DWI JAYA KIRANA; KORNEL SITANGGANG (Jurnal Bisnis dan Akuntansi, 2019)
The aim of this study is to test the influence of tax avoidance towards the cost of debt moderated by institutional ownership. In this research, tax avoidance measured by proxy of Book Tax Different (BTD) and Cash Effective Tax Rate (CETR). The population in this research is manufacturing firms that listed on Indonesia Stock Exchange (IDX) with 2015-2017 time periods. The amount of sample before outlier is 198 datas collected with purposive sampling method, then the amount of sample after outlier is 187 datas for first model and 186 datas for second model. Cross section data is used in this research. Multiple linear regression, determination coefficients, and partial test (t-test) is used with some help of programming data using SPSS (Statistical Product and Service Solution) 23th version to analize in this research. The result of this study indicate tax avoidance has not significant influence towards the cost of debt, and institutional ownership can’t moderate the relationship between tax avoidance and the cost of debt.